Mapping of knowledge on projects on justice sector facility development and human rights in Bangladesh since 2000 - Islam, Md. Rizwanul (School of Law, BRAC University, 2016)
This project was submitted to UNDP and implemented by School of Law, BRAC University, funded by UNDP and Uk aid as part of the JSF Project. Duration of the project was October 2014-July 2015.